Deep, helical, communal nesting and emergence in the sand monitor: ecology informing paleoecology?. (25th February 2018) - Doody, J. Sean; McHenry, Colin; Brown, Mike; Canning, Gordon; Vas, Gary; Clulow, Simon
Abstract: Dating back to 255 Mya, a diversity of vertebrates created mysterious deep helical burrows, often called Daimonelix (devil's corkscrews). A consensus function for these unique structures has not been reached, but the recent discovery of deep helical nesting burrows created by (extant) monitor lizards provides a unique opportunity to interpret Daimonelix and morphologically similar fossil burrows. We excavated a communal nesting warren of the Sand Monitor ( Varanus gouldii ) to test hypotheses for nesting and emergence behavior. First, we hypothesized that the nests of V. gouldii (in desert) would be deeper than those of the closely related V. panoptes (in savannah), because lower annual rainfall in the former (~350 mm vs. ~1000 mm) increases the threat of egg desiccation during the extremely long, dry season incubation period (~8 months). Second, we predicted that hatchlings would follow the nesting burrows of their mothers during emergence, because excavating their own emergence burrows would be energetically prohibitive due to the extreme depth and soil hardness. We excavated the warren to a depth of 4 m, finding 97 nests. As predicted, nest depth in V. gouldii (mean = 3.0 m, N  = 73) was significantly greater than in V. panoptes (mean = 2.3 m, N  = 52) from a previous study, and represents the deepest excavated ground nests of any vertebrate in the world. Contrary to our hypothesis, hatchlings ignored their mothers' nesting burrows, instead remarkably excavating their own emergence burrows. The communal nesting warrens and deep burrows of V. gouldii must have profound implications for the energetics of mothers and hatchlings, and perhaps for the social biology of the species. Although the function of the helix itself remains elusive, our results support the hypothesis that the extreme deep burrowing of Palaeocastor, Diictodon and other extinct animals was a response to arid conditions rather than temperature. Abstract : Dating back to 255 Mya, a diversity of vertebrates created mysterious deep helical burrows, often called Daimonelix ('devil's corkscrews'). A consensus about the function of these unique structures has not been reached; however, the recent discovery of deep helical nesting burrows created by extant monitor lizards provides a unique opportunity to interpret the Daimonelix and morphologically similar fossil burrows.